Defining Moments: Making Time for Virtual Visits and Catalyzing Better Cancer Care. Issue 6 (11th May 2020) - Anderson, Peter M.; Hanna, Rabi
ABSTRACT: Time is quite possibly a physician's most valuable asset, yet the tendency of almost all physicians is to be overly committed. How do we slowdown and make a meaningful difference? Virtual visits provide a new way to share and care without sacrificing the important nuances of face-to-face communication. When the Cleveland Clinic expanded our Distance Health capabilities in 2017 using virtual visits, we began a successful journey which provides cancer patients and their caregivers a new type of expert, unrushed cancer care access. This essay describes our current process for providing virtual visit access, preparing prior to the visit, keeping the visit as informative a possible, and closing the visit with a "distance health encounter" in the electronic medical record coupled with a summary and additional information via email.